NAVIGATING COMMUNICATION THROUGH THE CHALLENGES OF THE ACTUAL GEOPOLITICAL CONTEXT - Brînduşa Maria POPA (Journal of Defense Resources Management)
Today's complex geopolitical landscape, characterized by shifting power dynamics, cultural differences, information warfare and the rise of digital communication should consider mastering effective communication more critical than ever. Navigating these challenges demands special knowledge, skills, and a willingness to engage. Effective communication is essential for countries, organizations and individuals to successfully engage, negotiate, and collaborate in an increasingly interconnected yet, tension-filled world. Under such circumstances, communication should be viewed as an essential resource for governments, organizations and defense agencies and should be employed not just to provide orientation, coordinate activities and build trust. Still, governments and official communicators should remember that one of the major problems today is the public’s growing distrust in official sources. This distrust makes conveying accurate information more difficult and undermines efforts to counter global and national security threats.